2020
DOI: 10.1002/solr.202000268
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Bidentate Molecules Passivation Strategy for High‐Performance and Stable Inorganic CsPbI2Br Perovskite Solar Cells

Abstract: Cesium-based all-inorganic perovskites have witnessed extraordinary advances owing to their eye-catching thermal-resistance and photoelectric properties in optoelectronics and photonics application, including solar cells, [1-5] light-emitting diodes, [6,7] photodetectors, [8,9] nanolasers application, [9,10] and so on. In particular, inducing a prominent trade-off between the light absorption and phase stability in comparison with CsPbBr 3 and CsPbI 3 perovskites, [11-13] the mixed-halide inorganic CsPbI 2 Br … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 83 publications
0
18
0
Order By: Relevance
“…Annihilating such defects states by introducing organic molecules embracing functional groups possessing Lewis base nature has been reported for the passivation of undercoordinated Pb 2+ ions. Li et al [ 224 ] developed a passivation strategy by introducing bidentate molecules to achieve an efficient defect passivation and crystallization modulation, thus realizing compact and pinhole‐free CsPbI 2 Br films. It was suggested that the introduction of the bidentate molecules improved the grain size of the film and effectively reduced trap density and in so doing suppressed the unfavorable carrier recombination.…”
Section: Engineering Strategiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Annihilating such defects states by introducing organic molecules embracing functional groups possessing Lewis base nature has been reported for the passivation of undercoordinated Pb 2+ ions. Li et al [ 224 ] developed a passivation strategy by introducing bidentate molecules to achieve an efficient defect passivation and crystallization modulation, thus realizing compact and pinhole‐free CsPbI 2 Br films. It was suggested that the introduction of the bidentate molecules improved the grain size of the film and effectively reduced trap density and in so doing suppressed the unfavorable carrier recombination.…”
Section: Engineering Strategiesmentioning
confidence: 99%
“…[ 20,240,241 ] On the contrary, a large number of reported additives have weak interaction with Pb, resulting in a relatively labile passivation effect. Li et al [ 224 ] described a method for facial passivation that utilizes the bifunctional molecule 2‐(2 0‐thienyl)pyridine (2‐ThPy) to achieve both crystallization modulation and efficient defect passivation, resulting in high‐quality CsPbI 2 Br films. In comparison with its monodentate counterparts, 2‐methyl pyridine (2‐MPy) and 2‐methyl thiophene (2‐MTh), 2‐ThPy can strongly anchor Pb ions via S atoms in thienyl and N atoms in pyridyl, which are more conducive to delaying crystallization and accurately passivating halogen vacancies.…”
Section: Engineering Strategiesmentioning
confidence: 99%
“…[15,16] To address these issues, chemical composition engineering such as Rb þ , [17] Ba 2þ , [18] Eu 2þ , [19] In 3þ , [13] CH 3 COO À (Ac À ), [20] and Cl À [13] have been utilized to improve film morphology and enhance α phase stability of CsPbI 2 Br perovskite. Meanwhile, 4-aminobenzoic acid (ABA), [21] guanidinium hydrobromide (GABr), [22] 2-(2 0 -thienyl)pyridine (2-ThPy) [23] and other molecules have been introduced in precursor to passivate CsPbI 2 Br perovskite films, through the coordination of…”
Section: Introductionmentioning
confidence: 99%
“…is a prerequisite for high-efficiency PSCs. Therefore, various strategies in both the film fabrication and posttreatments, such as different crystallization control methods, [31,32] doping, [33][34][35][36][37][38] additive engineering, [39,40] interface engineering, [16,30,[41][42][43] etc., have been adopted to improve the quality of CsPbI 2 Br films. Among these strategies, additive engineering with the introduction of additives into the perovskite precursor solution in the film fabrication process is a simple and effective means to modulate the crystallization and improve film quality.…”
Section: Introductionmentioning
confidence: 99%
“…Most researchers focus on organic small molecules or polymers as additives in perovskite precursors. [39,40] However, the main effect of these additives is to control the crystal growth or passivate the defect states of the perovskite film, while it has a weak effect on the nucleation process.…”
Section: Introductionmentioning
confidence: 99%